2023
DOI: 10.1265/ehpm.23-00020
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits TGF-β1–induced fibrotic effects in human pterygium fibroblasts

Jianwu Fan,
Shuang Wei,
Xiaoyan Zhang
et al.

Abstract: Background Resveratrol is a polyphenolic phytoalexin which has the properties of anti-oxidant, anti-inflammatory and anti-fibrotic effects. The aim of this study was to investigate the anti-fibrotic effects of resveratrol in primary human pterygium fibroblasts (HPFs) and elucidate the underlying mechanisms. Method Profibrotic activation was induced by transforming growth factor-beta1 (TGF-β1). The expression of profibrotic markers, including type 1 collagen (COL1), α-sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Numerous in vitro and in vivo studies have highlighted the ability of resveratrol to attenuate fibrosis via inhibition of the canonical (Smad 2/3) and non-canonical TGF-β signaling pathways [ 92 , 93 , 94 , 95 , 96 ]. An investigation conducted on rat lung tissue revealed that the introduction of resveratrol led to a significant downregulation in the protein and RNA expression of TGF-β1, α-SMA, Smad3/4, p-Smad3/4, CTGF, collagen and p-ERK1/2 [ 93 ].…”
Section: Major Plant-derived Compounds That Modulate Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous in vitro and in vivo studies have highlighted the ability of resveratrol to attenuate fibrosis via inhibition of the canonical (Smad 2/3) and non-canonical TGF-β signaling pathways [ 92 , 93 , 94 , 95 , 96 ]. An investigation conducted on rat lung tissue revealed that the introduction of resveratrol led to a significant downregulation in the protein and RNA expression of TGF-β1, α-SMA, Smad3/4, p-Smad3/4, CTGF, collagen and p-ERK1/2 [ 93 ].…”
Section: Major Plant-derived Compounds That Modulate Fibrosismentioning
confidence: 99%
“…Guo et al described the cardiovascular protective effects of resveratrol, primarily attributed to its modulation of the non-canonical TGF-β/ERK1/2 signaling pathway [ 95 ]. Resveratrol treatment of isolated pterygium fibroblasts inhibited TGF-β1-induced proliferation, migration, contractility and expression of α-SMA, fibronectin and collagen type I [ 92 ]. Resveratrol treatment attenuated the activation of non-canonical p38 MAPK and PI3K/Akt pathways in these studies.…”
Section: Major Plant-derived Compounds That Modulate Fibrosismentioning
confidence: 99%